2004
DOI: 10.3164/jcbn.35.71
|View full text |Cite
|
Sign up to set email alerts
|

Serum Nutritional Components and Dietary Food Intake of People Living in a Remote Hilly Village in Eastern Nepal

Abstract: Summary Serum nutritional components and food intake were examined in Nepalese (127 males and 163 females aged 4 to 72 years) living in a remote hilly village (area A and B, area A is located at a relatively lower altitude and is warmer) in the eastern region of Nepal. Mean values of height and weight for the groups covering ages 4 to 19 of both sexes and in both areas increased with age. The mean BMI value for each age group was mostly under 22, and the BMI correlated with age, and with systolic and diastolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Compared with the normal range of TC (150-230 mg/dl), the mean TC level was at the lower range of normal levels (13), whereas the mean value of TG was at the higher range of normal levels in this study. Similar findings of high TG levels have been reported previously for other people (132-165 mg/dl in a remote hilly village, 175 mg/dl for the males in the Itahari district, 98-134 mg/dl for both sexes in the Chitwan district) in Nepal (4,17,18) and 23 to 72-yearold males (126.0±0.9 mg/dl) in Korea (19). The large intake of cereals containing much carbohydrate may have contributed to the higher serum TG level because excess carbohydrate intake is converted to fat in the human body.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Compared with the normal range of TC (150-230 mg/dl), the mean TC level was at the lower range of normal levels (13), whereas the mean value of TG was at the higher range of normal levels in this study. Similar findings of high TG levels have been reported previously for other people (132-165 mg/dl in a remote hilly village, 175 mg/dl for the males in the Itahari district, 98-134 mg/dl for both sexes in the Chitwan district) in Nepal (4,17,18) and 23 to 72-yearold males (126.0±0.9 mg/dl) in Korea (19). The large intake of cereals containing much carbohydrate may have contributed to the higher serum TG level because excess carbohydrate intake is converted to fat in the human body.…”
Section: Discussionsupporting
confidence: 90%
“…A support system for improving their nutritional status is needed for this group. Table 10 Comparison of daily average nutrient intakes of Nepalese Nutrient Sherpa (1) Itahari (2) Chitwan (3) Village (4) (A) Village (4)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 10 summarized the daily average nutrient intakes of Nepalese reported previously (1)(2)(3)(4). The nutrient intakes of the subjects in this study were lower than those of Nepalese shown in Table 10 as a whole.…”
Section: Discussionmentioning
confidence: 53%
“…For the past 30 years, we have been conducting dietary surveys in Nepal, in a mountain area (Mountain) (1), the southern Terai region (Level land) (Itahari district, an industrial (2) and Chitwan district, an agricultural (3) region) and a remote hilly village (Hills) (area A and B, area A is located at a rela-tively lower altitude and is warmer than area B) in the eastern area (4). These were selected depending on geographical belts (Mountain, Level land and Hills).…”
Section: Introductionmentioning
confidence: 99%